Phthalonitrile prepolymer and PAN blends : new strategy for precursor stabilization and pyrolytic char yield enhancement - Tay, Yu Shan (2022)
New polymer blends of polyacrylonitrile (PAN) and resorcinol-based phthalonitrile prepolymer (pPN) are studied as superior carbon precursors. pPN has a hyperbranch-like structure with multiple terminal nitrile groups available for chemical interactions. The addition of pPN into PAN significantly lowers the cyclization temperature by more than 15 °C during the oxidative stabilization stage which is unprecedented and highly desirable giving rise to a multitude of advantages during carbonization. The presence of pPN also leads to large synergy in char yield by due to the specific interaction between the nitrile terminal groups in the hyperbranch-like pPN and PAN chains. The char yield at 600 °C increased from 57.7% to a remarkable 69.0% when 10 wt% of pPN is added into PAN even though under the same condition the char yield of neat pPN itself is only 48.8%. Additional advantages of this new approach, i.e., large shrinkage reduction and property enhancement, are also observed in the carbonaceous materials obtained from the pPN/PAN blends. Raman spectra reveal that the carbon structure is retained when 10 wt% or less pPN is used.